Unemployment and Mortality : Evidence from the Great Recession - Nguyen, Ha (World Bank, Washington, DC, 2016)
Did unemployment in the Great Recession hurt people's health? The broad answer is no: job losses have statistically insignificant impacts on mortality. The exogenous sources of job losses in a U.S. county is the tradable job losses driven by external demand collapses during the Great Recession. The insignificant relationship holds for males and females, for all age groups, and for almost all categories of mortality. Three important exceptions are Alzheimer's, poisoning, and homicide.